A BIM-based framework for operation and maintenance of utility tunnels. (March 2020) - Yin, Xianfei; Liu, Hexu; Chen, Yuan; Wang, Yaowu; Al-Hussein, Mohamed
Highlights: The O&M of utility tunnels is investigated in detail. Extend BIM application to the O&M stage of utility tunnels. Monitoring, database and information visualization module make up the framework. Implementation example is conducted by designing and describing the user interface. Abstract: Underground utility tunnels are crucial for urban areas with high density in both population and number of buildings since they can tremendously improve the utilization of land resources. However, the operation & maintenance (O&M) of such underground tunnels is tedious and challenging, due to the fact that there is a lack of effective information technologies to facilitate O&M of utility tunnels. Although Building information modelling (BIM) technology is asserted to provide a game-changing solution to address the challenges encountered in the AEC industry, the use of BIM for operating and managing utility facilities in an efficient manner is rarely explored in the existing literature. To address this gap, a novel framework is proposed in this research to promote the sustainable O&M of utility tunnels with the support of BIM. Specifically, this framework encompasses three modules, namely, BIM model, O&M database, and monitoring system. A detailed description of each component of the proposed framework, as well as a preliminary user interface design, is presented in this paper. An implementation example is presented to provide the validation of the proposed framework. The preliminary results indicate the feasibility of the proposed framework in facilitating the information integration and communication of utility tunnels. This research contributes to the main body of knowledge by proposing a generic BIM framework for sustainable O&M of utility tunnels and formalizing data requirements as well as management workflow intended for utility tunnel O&M.